TECHNOLOGY OF MEDICINES AND GALENICAL PREPARATIONS: THE CASE OF PRESCRIPTION FORMULASFROM “ANTIDOTARIUM” NICOLAI BY NICHOLAS OF SALERNO - F. D. Voronov; I. N. Ruzhinskaya (Фармация и фармакология (Пятигорск), 2018)
Introduction. This study deals with the problem of similarity of the principles and approaches of drug technologies in the medieval manuscript “Antidotarium Nicolai” by Nicholas of Salerno with modern pharmaceutical technologies.The aim of study is a textual investigation of “Antidotarium Nicolai”, a detailed research of the content of the manuscript, recipes and technologies for making medicines.Materials and methods. In order to achieve this goal, eighty-five recipes of “Antidotarium Nicolai” have been identified, systematized and analyzed in a documentary translation from medieval French. An interdisciplinary study of the content of the manuscript was carried out with the help of factor analysis of the historical source and modern scientific literature.Results and discussion. Having described the content and aspects of the prescriptions of “Antidotarium Nicolai”, the authors note the similarity of the technologies of drugs and galenical preparations with modern pharmaceutical technology, in particular, with the technology of pharmacy production. In “Antidotarium Nicolai” it is stated that preparations based on herbal medicinal raw materials may be second-line therapy agents for completing treatment after the application of basic pharmacological preparations.Conclusion. The results of this work reveal the potential for the use of herbal medicines in the conditions of modern evidence-based medicine, in particular, in the organization of long-term treatment and secondary prevention of chronic diseases in patients who need to maintain their ability to work, and provide them with a sufficiently high level of quality of life. A detailed translation of the full text of the manuscript, the analysis of its content in accordance with the requirements of rational pharmacotherapy and phytotherapy, further favors to identify the prospects for the development of new drugs, multi-component in their chemical composition with a wide range of therapeutic effects.